Designing a Cardiovascular Health App for Citizens Returning from Incarceration: Where You Start May Not Be Where You End Up. Issue 1 (September 2020) - Zachary, Wayne W.; Wilkin, Theresa; Puglisi, Lisa; Butler, Marc; Ferdousi, Ishita; Smart, Jerry; Pethkar, Prathmesh; Surkan, Pamela J
A mobile health (mHealth) smartphone app can help persons returning from incarceration better manage cardiovascular disease (CVD) and CVD risk factors during their re-entry period. A successful intervention to educate and increase self-efficacy in this population around cardiovascular health has potential to produce broad population health benefits. A participatory design (PD) approach was used to define the features and functionality of such an intervention in the form of a smart phone app. The PD process forced the research team to view CV health in the broader context of other challenges that RCs face day to day. It also led to a broadening of the process to include other stakeholders that work closely with RCs, and to explore how these challenges affect the re-entry process. Ultimately, PD led to an app design that emphasized a common problem-solving approach that can be applied to a broad range of problems. An interactive prototype of the app's interface was assessed by a sample of RCs, users, with consensus that the problem-areas were appropriate and that the app was easy to use and to navigate. A quantitative assessment with the System Usability Survey instrument, yielded an average score of 81.5, placing it in the 90th percentile.